Reflecting on international educative experiences: developing cultural competence in pre-service early childhood educators - Anderson, Haley (Kansas State University, 2016)
The purpose of this literature review was to examine existing literature related to international experiences of early childhood pre-service educators. Given the unique opportunity for study abroad as a potential part of the college or university curriculum, the present discussion focuses on the question: what is the relationship between international experiences and pre-service early childhood educators’ cultural competence? More specifically, the following sub-questions were examined: 1) How is cultural competence defined across the literature? 2) What theories are applied to understand the effect of international experiences on the cultural competence of pre-service educators? 3) What pedagogical strategies are most frequently applied to develop cultural competence among pre-service educators? 4) What evidence is provided that pre-service educators changed (if at all) as a consequence of international immersion? A systematic literature search was conducted to locate original published studies that reported on the cultural competence of pre-service early childhood educators after international experiences. Detailed analysis of the articles revealed positive outcomes on pre-service educators who engaged in international educative experiences. Pedagogical strategies such as immersion and critical reflection led to pre-service educators’ self-reports of gains in personal and professional growth, cultural awareness, cultural sensitivity, and cultural competence. These findings warrant consideration by higher education, teacher education programs, and practice and research organizations. Further research examining the longevity of impact of international experiences on early childhood educator cultural competence in the classroom is suggested.
Keywords: Early childhood; Pre-service; Culture; International; Study abroad